ANALISIS PENGGUNAAN OLI BEKAS PADA MESIN PENYANGRAI KACANG KAWANGKOAN DI DESA KANONANG DUA - MOH. FIKRI POMALINGO (Pendidikan Teknik Mesin, 2021)
Used oil is an alternative fuel causing a number of problems. In terms of fuel consumption, the used oil consumption lasts longer. It also causes slow combustion because used oil has to reach a certain point in order to burn. The purpose of this study was to analyze the impact that occurs when the use of this machine continues to be implemented. This impact can be in the form of reducing the amount of waste and environmental safety from pollution. The method used in this research were a survey to obtain primary data, machine testing for, and calculations using the appropriate parameters. The results obtained that the kawangkoan peanuts roaster machine was able to roast in 10 minutes. This time is faster than the manual method that has been done so far. Fuel consumption reaches 0.8 liters / one roast. If this value is calculated with the number of kawangkoan peanuts craftsmen who reach 50 people according to data obtained from the village, it is certain that the amount of oil required for special roasting every year reaches 730,000 liters. This result is more than the amount of waste generated by vehicles in Minahasa which reaches 718,744 liters/year.